Handel emisjami do powietrza jako instrument polityki klimatycznej - Borys, Grażyna (Air emissions trading as an instrument of climate policy, 2006)
The objective ofthe hereby article is to present trading in the right to emit greenhouse gases to the air, as an instrument of climate policy implementation. The aim of such instrument is to minimize costs of the policy, which Poland has been carrying out as the result of signing Kioto Protocol and undertaking an obligation to curb air emissions, following the European Union accession. The article provides reasons for this instrument implementation as well as its construction.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 279-288